Correlation and path analysis in mulberry silkworm, Bombyx mori L. (Lepidoptera: Bombycidae) (Journal of the Asiatic Society of Bangladesh, Science, 2014)
The correlation and path analysis for nine quantitative characters in sixty five varieties of silkworm, Bombyx mori L. have been investigated. Out of all contributing characters studied expected cocoon yield 100 dfls (ECY) showed significant positive associations with majority of the characters except filament size (FS) both at the phenotypic and genotypic levels. It suggested a strong association of these traits with yield. The direct and indirect effects of the component characters of ECY at phenotypic and genotypic levels were obtained separately. Here surviving percentage of larvae (SPL) and cocoon weight (CW) showed positive and high direct effect which indicated a true relationship as obtained from correlation values. Other characters showed positive correlations but the direct effects were either negative or negligible. In such a situation indirect causal factors are to be considered simultaneouslyJ. Asiat. Soc. Bangladesh, Sci. 40(1): 151-156, June 2014